Buying and selling online: Legal protection for consumers using e-commerce - Sisbiantoro, Dwi (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary Sciences, 2022)
The purpose of study is to review the performance of consumer protection guarantee institutions and their role in protecting consumer rights. National development is manifested through a democratic economic development system so that it is able to grow and develop the world to produce goods and services that are suitable for consumption by the community. The study used qualitative approach. The approach used descriptive analysis with literature study review. The result of study that there are several institutions authorized to protect consumers. They are National Consumer Protection Agency, Non-Governmental Consumer Protection Agency, Indonesian Consumers Foundation, Consumer Dispute Settlement Agency. These consumer protection institutions have their own roles in providing protection to consumers, such as receiving complaints about consumer protection from the public, collaborating with relevant agencies in an effort to realize consumer protection, supervising the implementation of consumer protection and resolving disputes related to consumer protection.